2017
DOI: 10.4238/gmr16019281
|View full text |Cite
|
Sign up to set email alerts
|

Targeting effect of microRNA on CD133 and its impact analysis on proliferation and invasion of glioma cells

Abstract: ABSTRACT. , a member of the microRNA-200 family, has been identified to be capable of suppressing glioma cell growth through targeting CREB1 or CD133. However, whether miR-200b affects the biological behavior (proliferation, invasion, and migration) of glioma cells is poorly understood. The aim of this study was to evaluate the effect of miR-200b on the biological behavior of glioma cells in vitro. inhibitor, and mimic control were transfected into conventionally cultured glioma U251 cells, followed by measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…And miR-200b is proved widely expressed in many tumors, including breast cancer, pancreatic cancer and GC [20]. Interestingly, miRNA-200b could inhibit the proliferation, invasion, and migration of glioma cells through targeting CD133 in glioma [21]. Moreover, Chen [22] has proved miRNA-200 could inhibit the growth of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…And miR-200b is proved widely expressed in many tumors, including breast cancer, pancreatic cancer and GC [20]. Interestingly, miRNA-200b could inhibit the proliferation, invasion, and migration of glioma cells through targeting CD133 in glioma [21]. Moreover, Chen [22] has proved miRNA-200 could inhibit the growth of melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Similarly, many studies have demonstrated that miR-200b inhibits glioma cell proliferation and invasion. More specifically, miR-200b can target different genes, including cAMP responsive element-binding protein 1 (CREB1), zinc finger E-box binding homeobox 2 (ZEB2), prominin 1 (PROM1), extracellular signal-regulated kinase 5 (ERK5), CD133 10 , 19 , 31 33 and lactate dehydrogenase A (LDHA), which is associated with glioma cell proliferation and invasion. Therefore, targeting LDHA by miR-200b is regarded as a promising therapeutic strategy in glioma.…”
Section: Mir-200 and Metastasis Of Gliomasmentioning
confidence: 99%
“… 9 It has been reported that miRNAs regulate cell growth associated with the development and metastasis of cancers. 10 Some miRNAs have been specifically implicated in glioma pathogenesis. For example, recent reviews have indicated that circulating miRNAs could be potential glioma biomarkers and reported that miRNAs are associated with drug resistance, which may have direct therapeutic implications.…”
Section: Introductionmentioning
confidence: 99%
“…Геном вирусов гепатита B кодирует микроРНК (miRNA). В последние годы наблюдается бурный рост работ по генной регуляции, связанный с открытием в геноме человека генов, кодирующих регуляторные молекулы -микроРНК, которые негативно регулируют экспрессию многих генов [1][2][3][4][5][6][7][8][9][10][11]. МикроРНК синтезируются из более длинных предшественников и не кодирует белки [1][2].…”
Section: Introductionunclassified